1978
DOI: 10.1115/1.3453989
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Response of Packets of Blades by The Finite Element Method

Abstract: The finite element method is used to study the free vibration of packets of blades. A packet of six shrouded blades is analyzed, only the tangential vibrations being considered. Results are obtained to establish the effect of certain parameters such as stiffness ratio, mass ratio, the number of blades in the packet, the effect of rotation and the position of the lacing wires. The dynamic response of a packet to periodic loading is also studied. The cases of engine order harmonic excitation and partial admissio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1983
1983
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Dynamic behaviors of bladed packets are studied. 1,2 In order to investigate the different number of groups on the dynamic behaviors of bladed disk, finite modeling is used to study the difference in dynamic behaviors of two structures with different groups of bladed packets. 3 A modeling method is used to analyze the bladed disk with shroud.…”
Section: Introductionmentioning
confidence: 99%
“…Dynamic behaviors of bladed packets are studied. 1,2 In order to investigate the different number of groups on the dynamic behaviors of bladed disk, finite modeling is used to study the difference in dynamic behaviors of two structures with different groups of bladed packets. 3 A modeling method is used to analyze the bladed disk with shroud.…”
Section: Introductionmentioning
confidence: 99%
“…Thomas and Belek [16] have also used finite element model for a group of blades with rectangular cross-section to find modal parameters in the tangential mode. Salama and Petyt [17] have used finite element model and periodical structural analysis of the tangential vibration of packeted blades; both the positions of the lacing wire and rotations were taken into account.…”
Section: Introductionmentioning
confidence: 99%
“…They also showed that the in-plane vibration characteristics of a symmetric cross section blade group could be predicted from an inference diagram for a two-blade group. Salama and Petyt (1978) did a similar study, but additionally examined the effects of various positioning arrangements for coupling wires between blades, the effects of finite radius of the disk (i.e., radially oriented blades), and the stiffening effects of rotation. This analysis constrained the geometry, and thus the mode shapes, to be symmetric.…”
Section: Introductionmentioning
confidence: 99%